The Aggregation Dilemma in Climate Change Policy Evaluation - Ingmar Schumacher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The results in this paper show that a policy maker who ignores regional data and instead relies on aggregated integrated assessment models will strongly underestimate the carbon price and thus the required climate policy. Using a stylized theoretical model we show that, under the mild and widely-accepted assumptions of asymmetric climate change impacts and declining marginal utility, an Aggregation Dilemma may arise that dwarfs most other policy-relevant aspects in the climate change cost-benefit analysis. Estimates based on the RICE model Nordhaus (2000) suggest that aggregation leads to around 26% higher total world emissions than those from a regional model. The backstop energy use would be zero in aggregated versions of the model, while it is roughly 1.3% of Gross World Product in the regionally-disaggregated models. Though the policy recommendations from fully aggregated models like the DICE model are always used as a benchmark for policy making, the results here suggest that this should be done with the reservations raised by the Aggregation Dilemma in mind.
Keywords: Q54; Q58; Q50; 330